2018
DOI: 10.3389/fmicb.2018.00845
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Clostridium difficile Isolates in China From 2010 to 2015

Abstract: Clostridium difficile infection (CDI) has become a worldwide public health problem causing high mortality and a large disease burden. Molecular typing and analysis is important for surveillance and infection control of CDI. However, molecular characterization of C. difficile across China is extremely rare. Here, we report on the toxin profiles, molecular subtyping with multilocus sequence typing (MLST) and PCR ribotyping, and epidemiological characteristics of 199 C. difficile isolates collected between 2010 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…Geographical heterogeneity and transcontinental dissemination have aroused more concerns about regional CDI surveillance. In China, although the state of dilemma introduced by CDI has been documented before [6,7], data are lacking in the central and western regions. To fill gaps in the epidemiological territory of CDI in China, the results in this study presented basic knowledge of the prevalence and mortality of HA-CDI, and helped to improve the recognition of patients at high risk for HA-CDI Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geographical heterogeneity and transcontinental dissemination have aroused more concerns about regional CDI surveillance. In China, although the state of dilemma introduced by CDI has been documented before [6,7], data are lacking in the central and western regions. To fill gaps in the epidemiological territory of CDI in China, the results in this study presented basic knowledge of the prevalence and mortality of HA-CDI, and helped to improve the recognition of patients at high risk for HA-CDI Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike the rest of East Asia, limited data have focused on the burden of CDI in China. Although few regional studies alarmed that the hyper-virulent C. difficile strain ST-1 (BI/NAP1/027), an epidemic strain in Europe and North America, has emerged in Chinese hospital settings, recent reports revealed that ST35, ST37 and ST3 were the most prevalent genotypes in mainland China [6,7]. Moreover, in consideration of the complex personnel mobility in medical institutions, the majority of CDI is hospital-acquired, and nosocomial transmission of C. difficile contributes greatly to the spread of different genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…1 ml of enrichment broth was alcohol shocked with an equal volume of absolute ethanol for 1 h. A volume of 100 μl supernatant was plated directly on selective cycloserine-cefoxitin-fructose agar plates (CCFA, Oxoid, UK) with 5% egg yolk after ethanol shock treatment and incubated in an anaerobic jar at 37°C for 48 h. Isolation of C. difficile was based on previously described methods, suspected colonies were further confirmed by the 16S rRNA gene [41]. All colonies were cultured on anaerobic medium in an anaerobic environment at 37°C.…”
Section: Isolation Of C Difficilementioning
confidence: 99%
“…The methods of MLST, toxin genes profile and PCR-Ribotyping was obtained according to previously reported [13,41]. The primers and the amplification conditions used for PCR ribotyping have been described previously [42].…”
Section: Multilocus Sequence Typing (Mlst) Toxin Gene Profile and Pmentioning
confidence: 99%
“…The concentration of the extracted DNA was determined using NanoDrop (ThermoScientific, Wilmington, DE, USA). PCR was performed using primers specific for toxins A and B (TcdA2), TcdC (TNC), and the 16S ribosomal RNA gene (16S rRNA) as control ( Fiedoruk et al, 2015 ; Fry et al, 2012 ; Griffiths et al, 2010 ; Lemee et al, 2004 ; Li et al, 2017 ; Liu et al, 2018 ; Murray et al, 2009 ). The sequences of the primers used are: TcdA2 F-50AGATTCCTATATTTACATGACAATAT30, R- 5´GTATCAGGCATAAAGT AATATACTTT3´; TNC F- 5´GAGCACAAAGGGTATTGCTCTACTGGC3´, R- 5´CCAGACACAGCTAATCTTATTTGCACCT3´; 16S rRNA F- 5´ACACG GTCCAAACTCCTACG3´, R-5´AGGCGAGTTTCAGCCTACAA3´.…”
Section: Methodsmentioning
confidence: 99%